Characterization Of Non-Metallic Waste Material Reinforced Polymer Composites. (2017) - Diwedi, R.K.; bhaskar, J.; Pandey, Pramod; Kumar, Satyendra
Abstract: Non-metallic waste has been a source of pollution everywhere. In this paper Neem wood particles and waste tyre rubber particles is taken as non-metallic waste. These particles (size 200 micron) were used as reinforcements for fabricating composites with thermosetting and thermoplastic polymer matrix. Epoxy resin was thermoset matrix and Polypropylene was thermoplastic matrix. Tensile and flexure strengths were evaluated and compared with both type of matrices. Neem wood particles reinforced epoxy composites were observed better than tyre particles reinforced epoxy composites in tensile modulus. Tensile strengths were reduced in both Neem and Tyre epoxy composites. Modulus of elasticity of Polypropylene reinforced with Neem and tyre particles composites were improved 400 times and tensile strength were improved 230 times more than Propylene. Water absorption was increasing with the filler content in both PP and resin based composites. But it was 0.5% by weight .